Evaluating the impact of economic agricultural policies during the reform era for major crops and crop rotations in Egypt: a policy analysis matrix approach - El-Kholei, Ahmed Mohammed Salah (2003)
In 1986, Egypt implemented a succession of comprehensive economic reforms both in the agriculture sector and more generally such as the Economic Reform and Structural Adjustment Program (ERSAP) of 1991. Since then, the agricultural sector has been gradually transformed from one characterised by central planning and governmental controls to one that is more free market oriented.